Micronutrient malnutrition, obesity, and chronic disease in countries undergoing the nutrition transition: potential links and program/policy implications - Eckhardt, Cara L. (International Food Policy Research Institute, 2006)
This paper discusses the potential long-term effects of micronutrient malnutrition in early childhood on obesity and related disease outcomes. The links between early micronutrient malnutrition, stunting, and subsequent short adult stature — emerging risk factors for obesity and associated chronic diseases—are reviewed. This paper also explores recent literature linking micronutrient malnutrition in adults to increased risk and severity of chronic disease. Finally, this paper discusses the program and policy implications of these relationships. This paper is not the result of a systematic literature review, but rather discusses relevant literature to bring attention to links between under- and over-nutrition that have not been widely considered. Conclusions: In children, micronutrient malnutrition is a cause of stunting and may be accompanied by metabolic adaptations that increase the risk of later obesity and related disease. In adults, deficiencies in key micronutrients may promote oxidative stress, folate deficiency may increase risk for heart disease, and zinc deficiency may be exacerbated in the presence of diabetes while also affecting glucose transport. Low fruit and vegetable consumption may additionally increase the risk of cardiovascular disease (CVD) and cancer through a variety of mechanisms. The importance of supporting programs and policies that address the spectrum of malnutrition, including micronutrient malnutrition and emerging obesity together, is stressed